Multiband enhanced absorption of monolayer graphene with attenuated total reflectance configuration and sensing application. (14th December 2016) - Wang, Nan; Bu, Lingbing; Chen, Yunyun; Zheng, Gaige; Zou, Xiujuan; Xu, Linhua; Wang, Jicheng
Abstract: An enhanced absorption of monolayer graphene is obtained in a multilayer film-based attenuated total reflectance configuration in the visible wavelength range. The enhanced absorption under transverse magnetic and electric conditions is associated with the excitation of the waveguide mode in the thin-film layer, which is verified by the numerical calculation of field profiles. The obtained results manifest that the model induces a high field enhancement at the graphene–dielectric interface with the resonant angle, which implies potential sensing applications. The magnitude of the figure of merit is found to be three times higher than that of a conventional surface plasmon sensor.